Correlation between Insertion Torque and Implant Stability Quotient in Tapered Implants with Knife-Edge Thread Design. (15th May 2018) - Baldi, Domenico; Lombardi, Teresa; Colombo, Jacopo; Cervino, Gabriele; Perinetti, Giuseppe; Di Lenarda, Roberto; Stacchi, Claudio
Abstract : Aim . To evaluate the correlation between insertion torque (IT) and implant stability quotient (ISQ) in tapered implants with knife-edge threads. Methods . Seventy-five identical implants (Anyridge, Megagen) were inserted by using a surgical drilling unit with torque control and an integrated resonance frequency analysis module (Implantmed, W&H). IT (N/cm) and ISQ were recorded and implants were divided into three groups (n = 25 ) according to the IT: low (<30), medium (30 < IT < 50), and high torque (>50). ISQ difference among groups was assessed by Kruskal-Wallis test, followed by Bonferroni-corrected Mann–WhitneyU -test for pairwise comparisons. The strength of the association between IT and ISQ was assessed by Spearman Rho correlation coefficient (α = 0.05 ). Results . At the pairwise comparisons, a significant difference of ISQ values was demonstrated only between low torque and high torque groups. The strength of the association between IT and ISQ value was significant for both the entire sample and the medium torque group, while it was not significant in low and high torque groups. Conclusions . For the investigated implant, ISQ and IT showed a positive correlation up to values around 50 N/cm: higher torques subject the bone-implant system to unnecessary biological and mechanical stress without additional benefits in terms of implant stability. This trial is registered withNCT03222219 .